Le bâtard royal Henri d'Angoulême dans l'ombre des Valois (1551-1586) - Micallef, Fabrice 1982- (Cahiers d'humanisme et renaissance, 2018)
"Based on important and diverse documentation, this book traces the rise of Henry of Angoulême (1551-1586), the first French royal bastard, who learned to overcome the stigma of his illegitimate birth. From the perspectives of the French monarchy, humanist circles, leaders of the Order of Malta, and political actors in Provence, this work looks at the construction of an uncommon social identity of the 'royal bastard,' in which princely quality and marginality mixed." --Publisher's description